Development and validation of a stability-indicating RP-HPLC method for determination of aripiprazole and its degradation products - Mijatović, Vesna; Zečević, Mira; Zirojević, Jelena (Archives of Pharmacy, 2023)
The aim of this study was to develop a stability-indicating RP-HPLC method for the analysis of aripriprazole and its degradation products in tablets. In addition, robustness was tested by applying the methodology of experimental design. The forced degradation study of aripiprazole was conducted in accordance with the ICH guidelines. The stability of the active pharmaceutical substance was tested under the conditions of hydrolysis in acidic, neutral and basic environments, thermal degradation, oxidation and photolysis. The active pharmaceutical ingredient was degraded under oxidation conditions, and the identity of the resulting degradation product, N-oxide, was confirmed by comparing the retention time and UV spectrum with the reference standard substance. Under the other conditions tested, the active pharmaceutical substance was found to be stable. The developed method RP-HPLC allowed the separation of degradation products and aripiprazole and was defined as a stability-indicating method. The stability indicating RP-HPLC method was validated for simultaneous qualitative and quantitative analysis of aripiprazole and its impurities. Accordingly, selectivity, linearity, precision, accuracy, limit of detection, limit of quantification, and robustness of the method were tested. The Box-Behnken experimental design was used in robustness testing.
Keywords: aripiprazole; liquid chromatography; Box-Behnken experimental design; forced degradation study; degradation products